В6.А-DYSFPRMD/GENEJ MICE AS A GENETIC MODEL OF DYSFERLINOPATHY - M. V. Korokin; E. V. Kuzubova; A. I. Radchenko; R. V. Deev; I. A. Yakovlev; A. V. Deikin; N. S. Zhunusov; A. M. Krayushkina; V. M. Pokrovsky; O. A. Puchenkova; K. D. Chaprov; N. V. Ekimova; et al. (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2022)
The aim of the work was behavioral and pathomorphological phenotyping of the mice knockout for the DYSF gene, which plays an important role in the development and progression of dysferlinopathy.Materials and methods. A B6.A-Dysfprmd/GeneJ (Bla/J) mice subline was used in the work. During the study, a muscle activity was determined basing on the following tests: "Inverted grid", "Grip strength", "Wire Hanging", "Weight-loaded swimming", Vertical Pole". Histological and immunofluorescent examinations of skeletal muscles (m. gastrocnemius, m. tibialis) were performed. The presence and distribution of the dysferlin protein was assessed, and general histological changes in the skeletal muscle characteristics of mice at the age of 12 and 24 weeks, were described. A morphometric analysis with the determination of the following parameters was performed: the proportion of necrotic muscle fibers; the proportion of fibers with centrally located nuclei; the mean muscle fiber diameter.Results. The "Grip strength" test and the "Weight-loaded swimming" test revealed a decrease in the strength of the forelimbs and endurance in the studied mice of the Bla/J subline compared to the control line. The safety of physical performance was checked using the "Wire Hanging" test and the "Vertical Pole" test, which showed a statistically significant difference between the studied mice and control. The coordination of movements and muscle strength of the limbs examined in the "Inverted Grid" test did not change in these age marks. Decreased grip strength of the forelimbs, decreased physical endurance with age, reflects the progression of the underlying muscular disease. Histological methods in the skeletal muscles revealed signs of a myopathic damage pattern: necrotic muscle fibers, moderate lympho-macrophage infiltration, an increase in the proportion of fibers with centrally located nuclei, and an increase in the average fiber diameter compared to the control. The dysferlin protein was not found out in the muscle tissues.Conclusion. Taking into account the results of the tests performed, it was shown that the absence of Dysf-/- gene expressionin Bla/J subline mice led to muscular dystrophy with the onset of the development of phenotypic disease manifestations at the age of 12 weeks and their peak at 24 weeks. Histopathological phenotypic manifestations of the disease are generally nonspecific and corresponded to the data of intravital pathoanatomical examination in diferlinopathy patients. The mice of the studied subline Bla/J are a representative model of dysferlinopathy and can be used to evaluate new therapeutic agents for the treatment of this disease.